Pay to Play? State Laws Related to High School Sports Participation Fees. Issue 3 (May 2019) - Eyler, Amy A.; Piekarz-Porter, Elizabeth; Serrano, Natalicio H.
Abstract : Context: Participation in high school sports can impact the physical and mental health of students and influence other positive social and economic outcomes. To maintain sports programs amidst school budget deficits, many districts are implementing sports participation fee policies. Although locally implemented, these district policies can be guided by state law. Objective: The main objective of this study was to assess state laws and regulations related to high school sports participation fees. Design: Codified statutes and administrative regulations were compiled for all 50 states and the District of Columbia using subscription-based services from LexisNexis and WestlawNext. A content assessment tool was developed to identify key components of school sports participation fee laws and used for summarization. Key components identified included legislation summarization, years in effect, whether it allows fees, whether there is any fee waiver, qualifications needed for fee waiver, whether there is a tax credit, and whether there is disclosure of implementation. State information was aggregated and doubled-coded to ensure reliability. Results: As of December 31, 2016, 18 states had laws governing sports participation fees; 17 of these states' laws allowed for such fees, whereas 1 state prohibited them. Most laws give authority to local school boards to set and collect fees. The laws in 9 states have provisions for a waiver program for students who cannot pay the fees, although they do not all mandate the existence of these waivers. Other content within laws included tax credits and disclosure. Conclusion: This analysis shows that states with laws related to school sports participation fees varied in scope and content. Little is known about the implementation or impact of these laws at the local level and the effect of fees on different student population groups. This warrants future investigation.